Ultra‐Fast Dendritic Growth Based on the Grafting of Fullerene Hexa‐Adduct Macromonomers onto a Fullerene Core. Issue 16 (23rd May 2016) - Sigwalt, David; Caballero, Rubén; Holler, Michel; Strub, Jean‐Marc; Van Dorsselaer, Alain; Nierengarten, Jean‐François
Abstract : A fullerene hexa‐adduct building block bearing an azide functionality was prepared in six steps, and grafted onto a central fullerene core under copper‐catalyzed azide–alkyne cycloaddition conditions. The resulting tridecafullerene derivative is a first generation dendrimer with 132 peripheral ethyl ester groups. This compound was characterized by different spectroscopic techniques ( 1 H and 13 C NMR, IR, UV/Vis), and by MALDI‐TOF mass spectrometry. Despite a high degree of fragmentation, the molecular‐ion peak was detected, and all the observed fragments originate from a fully clicked derivative. This shows that the construction of dendrimers in a single dendritic growth step from fullerene hexa‐adduct macromonomers is an efficient strategy to produce monodisperse compounds. Abstract : A fullerene hexa‐adduct building block bearing an azide functionality was prepared in six steps, and grafted onto a central fullerene core under copper‐catalyzed azide–alkyne cycloaddition conditions. The resulting tridecafullerene derivative is a first generation dendrimer with 132 peripheral ethyl ester groups.